Analysis of Factors Affecting Food Security in Tapal Kuda Region, East Java, Indonesia - Cahyaningrum, Kurnia Mega; Mulyo Aji, Joni Murti; Hani, Evita Soliha (Agro Bali : Agricultural Journal, 2025)
One of the biggest issues facing countries around the world, including the Tapal Kuda region, is food security. Due to the large and productive agricultural area, a variety of food crops, including vegetables, corn, and rice, can be produced. However, it has food insecurity that can be caused by a decrease in crop area, lack of irrigation, low technology, social and economic changes. The purpose of this study is to ensure that poverty levels, rice production, GDP (Gross Regional Domestic Product), and rice prices have an impact on food security in Tapal Kuda. The sampling method used in the study was used deliberately, namely the purposive method. The selected examples are seven districts in the Tapal Kuda region including Probolinggo, Pasuruan, Lumajang, Jember, Bondowoso, Situbondo and Banyuwangi Regencies. Panel data regression analysis is a technique used that involves panel data or variations of cross section data and time series data. The analysis was carried out by managing the data using the Eviews software. The findings of the study show that poverty and rice prices have a negative impact on food security in the Tapal Kuda region, GDP (Gross Regional Domestic Product) and rice production have a positive impact. Optimizing the government's commitment to developing programs based on increasing local food production to keep pace with population growth and ensuring public access to safe and quality food can increase food security.